Extracellular release of ILEI⁄FAM3C and Aβ is associated with the activation of distinct synapse subpopulation. (December 2021) - Nakano, Masaki; Mitsuishi, Yachiyo; Liu, Lei; Watanabe, Naoki; Saito, Takashi; Saido, Takaomi C.; Suzuki, Toshiharu; Nishimura, Masaki
Abstract: Background: Previously, we reported a novel role of a secretory protein ILEI (also referred to as FAM3C) in modulation of Aβ metabolism. ILEI binds to the γ‐secretase complex and enhances non‐specific degradation of Aβ precursor protein (APP) C‐terminal fragments to suppress Aβ production without inhibiting γ‐secretase activity. In mammalian brain, ILEI is expressed in neuronal cells and localized in the trans ‐Golgi network and the endocytic vesicles where Aβ is produced. Synaptosome fractionation analysis further indicated that ILEI is colocalized with APP and the γ‐secretase complex at the active zone‐docked synaptic vesicles. In this study, we investigated extracellular release of ILEI and Aβ. Method: Firstly, we developed ILEI‐specific sandwich ELISA. We applied microdialysis to simultaneously monitor ILEI and Aβ levels in the interstitial fluid of frontal cortex of freely moving humanized mutant APP‐knockin mice. Using reverse microdialysis, we also examined the effect of perfusion with agonist⁄antagonist for glutamate, GABA, and ACh receptors on extracellular ILEI or Aβ. ILEI levels in autopsied brains and CSF samples of AD patients were measured using ELISA Result: Extracellular release of ILEI and Aβ was dependent on neuronal activation and specifically on tetanus toxin‐sensitive exocytosis of synaptic vesicles. However, simultaneous monitoring of ILEI and Aβ revealed that a spontaneous fluctuation of ILEI inversely mirrored that of Aβ. Selective activation and inhibition of synaptic receptors differentially altered these levels. Only the evoked activation of AMPA‐type receptors resulted in opposing changes to ILEI and Aβ levels. Brain ILEI levels were selectively decreased in AD. CSF ILEI concentrations were correlated with levels of Aβ40 and Aβ42 and were lower in patients with AD and mild cognitive impairment than in non‐demented controls. Conclusion: Our results suggested that ILEI and Aβ were released from distinct subpopulations of synaptic terminals in an activity‐dependent manner, and ILEI negatively regulates Aβ production in specific synapse types. CSF ILEI might represent a surrogate marker for the accumulation of brain Aβ.